2021
DOI: 10.2147/copd.s263031
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation in a Post-COVID-19 World: Telerehabilitation as a New Standard in Patients with COPD

Abstract: Pulmonary rehabilitation (PR) is effective in reducing symptoms and improving health status, and exercise tolerance of patients with chronic obstructive pulmonary disease (COPD). The coronavirus disease 19 (COVID-19) pandemic has greatly impacted PR programs and their delivery to patients. Owing to fears of viral transmission and resultant outbreaks of COVID-19, institution-based PR programs have been forced to significantly reduce enrolment or in some cases completely shut down during the pandemic. As a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 86 publications
1
81
0
18
Order By: Relevance
“…As a preliminary response to prompt clinical practice implementations of remotely delivered pulmonary rehabilitation, several health care platforms included resources for tele-rehabilitation and home-based rehabilitation, including the homebased rehabilitation website: https://homebaserehab.net/ (accessed on 13 October 2021). Additional remotely delivered pulmonary rehabilitation recourses include the Canadian Thoracic Society pulmonary rehabilitation-endorsed program and guidance on virtual models of pulmonary rehabilitation from the Agency for Clinical Innovation in New South Wales, Australia [82,83].…”
Section: Pulmonary Rehabilitation During Covid-19 Pandemicmentioning
confidence: 99%
“…As a preliminary response to prompt clinical practice implementations of remotely delivered pulmonary rehabilitation, several health care platforms included resources for tele-rehabilitation and home-based rehabilitation, including the homebased rehabilitation website: https://homebaserehab.net/ (accessed on 13 October 2021). Additional remotely delivered pulmonary rehabilitation recourses include the Canadian Thoracic Society pulmonary rehabilitation-endorsed program and guidance on virtual models of pulmonary rehabilitation from the Agency for Clinical Innovation in New South Wales, Australia [82,83].…”
Section: Pulmonary Rehabilitation During Covid-19 Pandemicmentioning
confidence: 99%
“…Aside from home-based PR and tele-rehabilitation, this could include web-based tele-rehabilitation, center-based telerehabilitation and home-based tele-rehabilitation. Studies have found that home-based telerehabilitation can achieve clinically important gains in health-related quality of life [33][34][35].…”
Section: What Kind Of Recommendation For Future Pr Implementation?mentioning
confidence: 99%
“…The use of pulmonary telerehabilitation was expanded during the coronavirus disease 2019 (COVID-19) pandemic because standard rehabilitation programmes were suspended and to respond to the specialist rehabilitation needs of COVID-19 survivors following hospital discharge [ 77 ]. However, some significant issues have emerged including: some patients lack access to computers; methods and tools for programme evaluation are not standardised; and training and resources for health professionals is inadequate [ 78 ]. To overcome these problems, researchers have proposed models of pulmonary telerehabilitation in respiratory diseases patients, and rapidly implemented their use in clinical practice [ 79 ].…”
Section: The Burden Of Respiratory Treatmentsmentioning
confidence: 99%